PENGARUH PENDAPATAN ASLI DAERAH TERHADAP KEMANDIRIAN KEUANGAN DAERAH DI KABUPATEN/KOTA PROVINSI KALIMANTAN BARAT - Saputra, Edi; Sastrawan, Rahman; Patria, Andika (JURNAL LENTERA AKUNTANSI, 2025)
The purpose of this study is to measure how much the contribution of PAD, which includes parameters of regional taxes, regional levies, results of management of separated regional assets, and other PAD sources, affects the ability of regions to manage finances independently in the Regency/City of West Kalimantan Province. The approach uses an associative quantitative method, using secondary data taken from budget implementation report documents recorded at the West Kalimantan BPS during the 2020-2023 period. The hypothesis was tested using the WarpPLS application using the Structural Equation Modeling (SEM) reference. The conclusion of the study proves that regional original income, measured through parameters of regional taxes, regional levies, and results of management of separated regional assets, has a significant impact on regional financial independence. However, other variables in legitimate PAD do not show a significant effect on regional financial independence.